Apakah Praktik Keadilan Organisasional dalam Usaha Mikro, Kecil dan Menengah berpengaruh terhadap Loyalitas Kerja dan Komitmen Organisasi Karyawan Mereka? - Pande Putu Yuda Raditya Gunasta Putra; Antonius Sumarwan; Tantia Margaaret (Jurnal Bisnis dan Kewirausahaan)
This study aims to understand how organizational justice affects work loyalty and organizational commitment in MSMEs. Employees who are loyal and committed to their organisation are likely to contribute more to the sustainability of their organisation. Using data on 108 employees from 23 MSMEs analysed using hierarchical multiple regression, this study tested the hypotheses that procedural and distributive justice practices influence work loyalty and organizational commitment in MSMEs. The research findingsconfirm the hypotheses: procedural and distributive justice practices positively and significantly influence MSME employees’ loyalty and commitment to their organisations. Interestingly, the effect of distributive justice practices on employees’ loyalty and commitment is higher than the effect of procedural justice; the effect of the two types of justice practices on loyalty is higher than their effect on commitment to the organisation. This study provides empirical evidence of the positive impactof organizational justice practices in the context of MSMEs. Therefore, MSMEs need to practice distributive and procedural justice as these practices lead to increased employee loyalty and commitment.